Enhancing crop and labor productivity, profitability, and production economics through efficient crop diversification in Bangladesh: Comparing diversified cropping patterns in Dinajpur, Bangladesh - Washiq, Faisal; Hossain, Akbar; Aonti, Annika Jahan; Md. Mobinur Rahman; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Rice-based cropping systems have a significant role in attaining self-sufficiency in food production and are considered to be the major contributor to the nation’s food basket in Bangladesh. Nowadays concern has been raised over the sustainability of this system due to natural resource degradation (tillage practices, high wages of labor, and overuse of groundwater), reduction in profitability, and declining yield growth rates. Intensive tillage practices demand more resources, damage soil quality, and reduce crop yields and profit margins. Crop diversification, agriculture mechanization, and proper labor productivity may improve resource-use efficiency and increase the productivity and profitability of intensive cropping systems. This research study focuses on accelerating the transformation of our agrifood systems by introducing different diversified cropping options, especially highlighting the production economics, labor productivity, and mechanization for the northern part of Bangladesh. The research trial was established at the Bangladesh Wheat and Maize Research Institute (BWMRI) in Dinajpur, Bangladesh in August 2022.